Handbook of magneto-optical data recording : materials, subsystems, techniques - McDaniel, Terry W.; Victora, Randall H. (Noyes Publications, 1997)
Discusses many aspects of MO data recording, including the materials in use, techniques for achieving recording function, and storage device subsystems.
Keywords: Data disk drives.; CD-ROMs.; Computer storage devices.; Magnetooptical devices.; elektronické knihy; electronic books